2013
DOI: 10.3346/jkms.2013.28.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index, Smoking, and Blood Pressure on Survival of Patients with Surgically-Treated, Low Stage Renal Cell Carcinoma: A 14-Year Retrospective Cohort Study

Abstract: The association of body mass index, smoking, and blood pressure, which are related to the three well-established risk factors of renal cell carcinoma, and survival in patients with renal cell carcinoma is not much studied. Our objective was to evaluate this association. A cohort of 1,036 patients with low stage (pT1 and pT2) renal cell carcinoma who underwent radical or partial nephrectomy were enrolled. We retrospectively reviewed medical records and collected survival data. The body mass index, smoking statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
0
20
2
Order By: Relevance
“…Perioperative hypertension is associated with an increased risk of adverse events, including cardiovascular morbidity or even death [26,27]. Regarding long-term outcome, it was reported that pre-and postoperative hypertension negatively affects long-term survival in patients after renal or rectal cancer surgery [12,13]. However, the opposite effects of intraoperative hypertension were also reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative hypertension is associated with an increased risk of adverse events, including cardiovascular morbidity or even death [26,27]. Regarding long-term outcome, it was reported that pre-and postoperative hypertension negatively affects long-term survival in patients after renal or rectal cancer surgery [12,13]. However, the opposite effects of intraoperative hypertension were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Second, microenvironmental hypoxia, which is a common feature in solid cancer [33], might have been aggravated by intraoperative hypotension and thus promoted cancer aggressiveness and metastasis via hypoxia inducible factor mechanisms [34,35]. Third, hypoxia resulting from intraoperative hypotension might have augmented systematic inflammation [36] which enhances cancer recurrence and cancer-related death [37]. Interestingly, a recent study showed that individualized intraoperative blood pressure management reduced systemic inflammatory response syndrome and organ dysfunction after surgery…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity is considered a risk factor for RCC, survival has been shown to be more favorable in patients with a BMI that is higher than the underweight category. 53 Therefore, overaggressive weight reduction may not be beneficial.…”
Section: Obesity and Rccmentioning
confidence: 99%
“…[66][67][68][69][70] Perioperative blood pressure $150/100 mmHg negatively affects the overall survival in Korean patients with RCC. 46 Yet, in a study of RCC cases in the USA, a self-reported history of hypertension was associated with a better overall survival. 71 The biological mechanism underlying the relationship between elevated blood pressure and increased risk of RCC remains unknown.…”
Section: Hypertensionmentioning
confidence: 99%
“…44,45 Furthermore, Korean and German studies suggest that being underweight at the time of surgery worsens cancer-specific survival by more than four times that of normal weight individuals. 46,47 BMI is an imperfect measurement of body fat as it does not distinguish between fat and muscle and between visceral and subcutaneous fat. Based on the results of multiple Japanese studies, visceral obesity rather than BMI may be a more useful predictor of disease-recurrence survival rather than BMI since high visceral fat has been associated with longer cancer-specific survival and overall survival.…”
mentioning
confidence: 99%